2008
DOI: 10.1097/01.anes.0000296071.19434.1e
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cognitive Dysfunction after Major Noncardiac Surgery

Abstract: Cognitive dysfunction is common in adult patients of all ages at hospital discharge after major noncardiac surgery, but only the elderly (aged 60 yr or older) are at significant risk for long-term cognitive problems. Patients with POCD are at an increased risk of death in the first year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
1,125
11
65

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,280 publications
(1,241 citation statements)
references
References 52 publications
40
1,125
11
65
Order By: Relevance
“…Most previous studies that utilized the neurological assessments used in cardiac surgery studies failed to detect any cognitive dysfunction after non-cardiac surgery. More recent studies have identified other factors associated with cognitive dysfunction, i.e., age, preoperative level of education and postoperative complications are listed as risk factors, while the effect of type of anesthesia may be minor [9,15].…”
Section: Risk Factors and Proposed Mechanisms Of Cognitive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies that utilized the neurological assessments used in cardiac surgery studies failed to detect any cognitive dysfunction after non-cardiac surgery. More recent studies have identified other factors associated with cognitive dysfunction, i.e., age, preoperative level of education and postoperative complications are listed as risk factors, while the effect of type of anesthesia may be minor [9,15].…”
Section: Risk Factors and Proposed Mechanisms Of Cognitive Dysfunctionmentioning
confidence: 99%
“…Cognitive dysfunction may also be associated with increased long-term morbidity or mortality, premature withdrawal from the labor market and social welfare transfer payments [15,21].…”
Section: Social Impact Of Pocd and Efforts For Its Preventionmentioning
confidence: 99%
“…There is good evidence that major cardiac and non-cardiac surgical procedures may affect cognitive function [1][2][3][4][5]. The incidence of postoperative cognitive dysfunction (POCD) varies greatly with reported rates of 4% to 41% after major surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of postoperative cognitive dysfunction (POCD) varies greatly with reported rates of 4% to 41% after major surgery [5][6][7]. Most POCD cases recover within a few weeks following surgery and anesthesia [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation